Personality Characteristics of Patients With Pain. 2000
DOI: 10.1037/10376-009
|View full text |Cite
|
Sign up to set email alerts
|

Perceived optimism and chronic pain.

Abstract: The personality dimension of optimism is one aspect of the broader study of pain and draws a great deal of attention as a significant mediator of stress in several psychological domains, including health and clinical psychology. Because of its health-promoting effects-observed across various physical conditions-there has been growing speculation that optimism could influence the course and experience of pain. This hypothesis coincides with a burgeoning body of literature that suggests not only that psychologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 57 publications
0
16
0
8
Order By: Relevance
“…In his review of the optimism and pain literature published in 2000 [18], Garafalo suggested that the scant amount of completed research addressing the beneficial effects of optimism on pain were compelling but too preliminary to make any meaningful generalizations. He concluded by stating that further exploration of optimism’s role as a protective factor in the experience of pain was needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In his review of the optimism and pain literature published in 2000 [18], Garafalo suggested that the scant amount of completed research addressing the beneficial effects of optimism on pain were compelling but too preliminary to make any meaningful generalizations. He concluded by stating that further exploration of optimism’s role as a protective factor in the experience of pain was needed.…”
Section: Discussionmentioning
confidence: 99%
“…In 2000, Garofalo conducted a review of the then scant body of literature specifically addressing whether optimism confers any benefit for the experience and management of chronic pain [18]. At the time, the influence of optimism on individuals’ experiences of chronic pain, or any type of pain for that matter, had never been systematically examined.…”
Section: Introductionmentioning
confidence: 99%
“…26 It is a valid, reliable, and brief measure that assesses the general worldview that good things will happen to the respondent. 11 Scores range from 0 to 48, with higher scores indicating a more positive life outlook. The Health Optimism Scale is a measure of optimism specific to health.…”
Section: Methodsmentioning
confidence: 99%
“…En este sentido, Garofalo (2000) establece que las variables psicológicas están implicadas de forma importante en la experiencia de dolor, al tiempo que presentan un papel fundamental en la respuesta que los pacientes presentan al tratamiento. Así, Turk (1996) establece que el desarrollo y manifestación del dolor y la fatiga características de la fibromialgia, están originadas por un proceso de condicionamiento respondiente.…”
unclassified